2017
DOI: 10.1002/ejoc.201701324
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Carbonyl Group Controlled Coupling of Isatin Oximes with Arylboronic Acids To Prepare N‐Aryloxindole Nitrones

Abstract: A variety of (E)‐N‐aryloxindole nitrones were prepared in good to excellent yields by using a copper‐catalyzed coupling reaction of isatin oximes and arylboronic acids under mild conditions. Various arylboronic acids that contain sensitive functional groups were tolerated in the transformation, and detailed studies show that the carbonyl group of the isatin oximes serves as a ligand to control the formation of the (E)‐oxindole nitrones. This method to prepare (E)‐N‐aryloxindole nitrones was easily performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…[10] Furthermore, the Brandi-Guarna rearrangement, namely, the NÀO bond cleavage of 5-spirocyclopropane-isoxazoline cycloadducts produced by the cycloaddition of nitrones and methylenecyclopropanes, which can then undergo rearrangement to afford piperidin-4-ones owing to the highly strained spirocyclopropane ring, has been successfully applied to natural product synthesis. [11] During our studies on the preparation and cycloaddition of isatin nitrones, [12,13] we surmised that the carbonyl group in isatin nitrones could act as a directing group and coordinate with a catalyst to control diastereoselectivity in the cycloaddition of isatin nitrones and methylenecyclopropanes. [14] Sequential reduction of the cycloadducts would provide furo [2,3-b]indolines through interrupted Fischer indolization.…”
Section: Communicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…[10] Furthermore, the Brandi-Guarna rearrangement, namely, the NÀO bond cleavage of 5-spirocyclopropane-isoxazoline cycloadducts produced by the cycloaddition of nitrones and methylenecyclopropanes, which can then undergo rearrangement to afford piperidin-4-ones owing to the highly strained spirocyclopropane ring, has been successfully applied to natural product synthesis. [11] During our studies on the preparation and cycloaddition of isatin nitrones, [12,13] we surmised that the carbonyl group in isatin nitrones could act as a directing group and coordinate with a catalyst to control diastereoselectivity in the cycloaddition of isatin nitrones and methylenecyclopropanes. [14] Sequential reduction of the cycloadducts would provide furo [2,3-b]indolines through interrupted Fischer indolization.…”
Section: Communicationsmentioning
confidence: 99%
“…[15] To our delight, adding Cu(OAc) 2 (10 mol%) as catalyst afforded product 3 aa in 66% yield and 5:1 dr after only 24 h ( Table 1, entry 3). The yield of 3 aa decreased when using other copper salts, while the dr of 3 aa was increased to 20:1 using Cu(II), and decreased to 3:1 using Cu(I) ( Table 1, entries [10][11][12]. Solvent screening showed that product 3 aa was afforded in moderate yields in toluene, MeCN, THF, and DMSO; with diastereomeric ratios ranging from 1.6:1 to 4:1 ( Table 1, entries 4-7).…”
Section: Communicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrones, as 1,3-dipolars, have received much attention in synthetic organic chemistry, not only because they are versatile building blocks to access N,O-containing heterocycles and natural products through the stereoselective [3 + 2]-cycloadditions with various dipolarophiles but also because many other novel transformations involving nitrones have been developed in recent years . A large number of protocols have been intensively investigated, such as oxidation of a secondary hydroxylamine/amine, condensation of a carbonyl compound with a hydroxylamine, and N -alkylation of an oxime ether or oxime; these are the most common strategies for the synthesis of nitrones. Despite the efficiencies of these methods, most of the methodologies have been limited to aldonitrones, and reports on ketonitrone chemistry remain scarce, owing to general kinetic instability of ketonitrones unless an electron-withdrawing group is present …”
mentioning
confidence: 99%